Investigating the effect real options on stock return a panel: Var approach - Mostafa Heidari Haratemeh; Behnam Ebrahimi (New Applied Studies in Management, Economics & Accounting)
In this study, evidence is presented that shows the positive stock return-volatility relationship at the firm level is due to firm's real options. Therefore, the purpose of the study was to investigate the effect of real option on the relationship between stock returns and its volatility at the company level.  In the real options theory, it can be deduced: a) that the positive stock return-volatility at the firm level for those firms with more real options is much stronger and that the level of the sensitivity of the firm's stock return in response to the changes in the stock return volatility is significantly reduced due to the use of real options. b) that the positive relationship between stock return and return volatility at the firm level for companies that have investment opportunities are stronger. While, this relationship for asset-based companies is weaker.  In other words, the return – volatility relationship is stronger for newly established companies, small companies, companies with modern research and development and finally companies with high growth rates. c) That, the relationship between return – volatility for companies that have fewer restrictions and greater capabilities to better respond to uncertain demands (greater flexibility) are much stronger. In the real options models, managerial flexibility leads to greater firm's value convexity function. Thus, according to the theory of Jensen’s inequality, sensitivity of the firm's value due to volatility in firm's underlying assets, while increasing, it should help to strengthen the company's flexibility to the changes in investment decisions and operations.